CLASSIFICATION OF SLAVIC LANGUAGES: EVOLUTION OF DEVELOPMENTAL MODELS - BLAŽEK, VÁCLAV (Slavia Occidentalis, 2020)
The contribution summarizes nearly all the models of classification of the Slavic languages, presented in the past 350 years, from simple enumeration through the qualitative and quantitative approaches, typically leading to the developmental models depicted as tree-diagrams, as well as the linear and net models. The individual models, especially the quantitative ones, are discussed in detail and, finally, correlated with accounts of Byzantine historians.